TRANSFORMATIVE LEARNING TERHADAP PELESTARIAN PERMAIANAN TRADISIONAL PADA ANAK JALANAN DI LINGKUNGAN KAMPOENG DOLANAN SURABAYA - NurSekti, Marita (Universitas Negeri Surabaya, 2022)
Kampoeng Dolanan is a traditional game community that preserves culture as an ancestral heritage with the values and philosophies contained in it. The results of the study describe that there is a transformative learning process in the form of providing changes in the habits or behavior of street children that have an impact on the behavior, environment and economy around the village. At each impact, street children and the community around the village get an introduction, play, and preserve traditional games from the dolan nang kampoeng activities, festivals and competitions with children around the neighborhood as well as the general public or visitors who come to participate in Kampoeng dolanan.